2020
DOI: 10.3390/s20061599
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Static Radar Network with Ultra-Wideband Radio-Equipped Devices

Abstract: A growing number of devices, from car key fobs to mobile phones to WiFi-routers, are equipped with ultra-wideband radios. In the network formed by these devices, communicating modules often estimate the channel impulse response to employ a matched filter to decode transmitted data or to accurately time stamp incoming messages when estimating the time-of-flight for localization. This paper investigates how such measurements of the channel impulse response can be utilized to augment existing ultra-wideband commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 40 publications
(48 reference statements)
1
52
0
Order By: Relevance
“…Information (including raw signal, bandpass signal, motion filtered signal, and detection list) extracted from the reflected signals is used to estimate the locations of targets with an accuracy at the decimeter level. To improve the accuracy, a multi-static is deployed in [129] to track a person in real-time by determining the difference between the channel impulse response with the presence of a new object and that of the previous one without the object. The location of the object can be found with the mean error of only 3 cm by applying a leading edge detection algorithm on the difference between This work is licensed under a Creative Commons Attribution 4.0 License.…”
Section: A: Crowd Detectionmentioning
confidence: 99%
“…Information (including raw signal, bandpass signal, motion filtered signal, and detection list) extracted from the reflected signals is used to estimate the locations of targets with an accuracy at the decimeter level. To improve the accuracy, a multi-static is deployed in [129] to track a person in real-time by determining the difference between the channel impulse response with the presence of a new object and that of the previous one without the object. The location of the object can be found with the mean error of only 3 cm by applying a leading edge detection algorithm on the difference between This work is licensed under a Creative Commons Attribution 4.0 License.…”
Section: A: Crowd Detectionmentioning
confidence: 99%
“…Global Navigation Satellite System (GNSS), and Zigbee signals are potential solutions for social distancing verification (Al-Suwaidi and Zemerly, 2009, Laoudias et al, 2018, Ledergerber and D'Andrea, 2020, Mazuelas et al, 2009, Niu et al, 2015. Sensor technologies pick up ultrasound, inertial, visible light or thermal frequency signals from specific tags attached to the users (Jovicic and Engineer, 2016, Kok et al, 2015, Szajewska, 2017, Tiemann and Wietfeld, 2017.…”
Section: Related Workmentioning
confidence: 99%
“…In addition, they demonstrated that they can detect vehicles with channel sounders [ 14 ]. In [ 15 ], Ledergerber et al present a multi-static radar solution based on UWB transceivers. To localize the person, they inspect the mean and the variance of the measured CIR and determine the position of a person by a particle filter.…”
Section: Related Workmentioning
confidence: 99%